Proposition of critical levels of nutrients in citrus leaves, grown in a subtropical climate, for fresh market fruit production - Krug, Amanda Veridiana; Papalia, Daniéle Gonçalves; Marques, Ana Luiza de Lima; Hindersmann, Jacson; Soares, Vanessa Marques; Grando, Douglas Luiz; Moura-Bueno, Jean Michel; Trapp, Talita; Rozane, Danilo Eduardo [UNESP]; Natale, William; Brunetto, Gustavo (Elsevier, 2023)
Critical levels (CL) and sufficiency ranges (SR) of nutrients in citrus leaves for fruit production for fresh market consumption may help in defining the real need for fertilizer application in orchards, such as those located in tropical and subtropical soils, which have low natural fertility. The study aimed to establish and compare the nutritional patterns obtained by the Composition Nutritional Diagnosis method (CND) in citrus grown for consumption for fresh, in a subtropical climate and then generate CL and SR in leaves. A database was used with fruit production and leaf nutrient contents obtained in the 2016/17, 2017/18, 2019/20 and 2020/21 harvests in non-irrigated commercial orange and tangerine orchards. The multivariate CND calculation method was used. The CND method was effective in diagnosing the nutritional status of citrus, regarding the concentration of the nutrients N, P, K, Ca, Mg, S, Cu, Fe, Mn, Zn and B in deficient, adequate and excessive concentrations. The CL calculated were 18, 1.2, 9.0, 25, 2.8 and 3.0 g kg−1 of N, P, K, Ca, Mg and S, respectively, and 117, 45, 97, 66 and 19 mg kg−1 of B, Cu, Fe, Mn and Zn, respectively. The existing recommendation in the regional recommendation guide for citrus may be overestimating the need for application of the micronutrients. The SRs established from the CND index are different from those obtained in other countries and regions. Multi-nutrient associations were more effective than single nutrient analysis in expressing that limitation of a particular element can reduce citrus productivity. The adoption of the nutritional standards for macronutrients obtained may allow the rational use of fertilizers in citrus orchards, with an improvement in the nutritional balance of the plants, which will consequently have greater yields.
Keywords: CND; Fertilization in orchards; Mandarine; Multi-nutrient associations; Nutritional status; Orange; Tangerine